Pengaruh Konsentrasi Etanol Terhadap Unjuk Kerja Dan Emisi Gas Buang Motor Bensin Pada Kondisi Idle Dan Dengan Standar Ece 83-04 - Prawoto, Prawoto; Nugroho, Bagus Anang (Semesta Teknika, 2006)
This paper describes a study an influence of ethanol concentration in premium-ethanol fuel blends on vehicle performance and exhaust gas emissions. The study is based on the vehicle test on chassis dynamometer. Exhaust gas emission was measured on idle condition and using ECE standard regulation No. 83-04. Three compositions were performed on the first step, which are 3%, 10% and 20% of volume. Performance and emission results were compared to the test results on the same vehicle fuelled with 100% premium and pertamax. The test results have shown that increasing concentration of ethanol will increase torque and power, reduce CO and HC emission, except on idle condition. 10% ethanol concentration have identical performance characteristic with the same vehicle fuelled with pertamax, with 60% less CO emission on idle condition and 30% less when using ECE 83-04 standard.